Isoguaiacins, Arylnaphthalene Types Identified as Novel Potent Estrogenic Signaling Molecules from Larrea nitida. (25th August 2015) - Jeong, Si‐Yeon; Ahn, Hye‐na; Bae, Gyu‐Un; Chang, Minsun; Liu, Xiyuan; Rhee, Hee‐Kyung; Lee, Joongku; Chin, Young‐Won; Oh, Sei‐Ryang; Song, Yun Seon
<x xml:space="preserve">Abstract</x> <boxed-text content-type="graphic" id="bkcs10437-blkfxd-0001" position="anchor" orientation="portrait"> </boxed-text> Two isoguaiacins, arylnaphthalene type compounds 1 and 2, were isolated from Larrea nitida. Their structures were evaluated by ER binding and ERE transcription assay.